For Quality Education: The Reality of Training in Regional Education and Training Centres and Possible Alternatives for Improving Training (Sidi Kacem Centre) - FAIK, Toufik; Laabaissi, Thami; EL HAMMOUCHI, Abdelaziz (International Journal of Language and Literary Studies, 2025)
This study examines the challenges faced by trainees at the Sidi Kacem Centre for Education and Training Professions, with a focus on the impact of these challenges on the quality of training. The research addresses critical issues in infrastructure, human resources, pedagogical methods, and the effectiveness of scientific research. The primary objective is to diagnose the current situation and propose strategic solutions to enhance training quality at the centre. An analytical approach was employed, utilizing a questionnaire to dissect the components of the issue and explore the interrelationships between its various factors. The study surveyed 50 participants from the centre, with data analysis conducted using SPSS software. The findings reveal that inadequate infrastructure significantly impedes training quality and highlight the necessity for both initial and ongoing professional development. The study also underscores the importance of effective pedagogical strategies in improving professional qualifications and the pivotal role of technology in shaping the educators of tomorrow. Furthermore, the results emphasize the urgency of accelerating intervention projects to equip trainees with essential 21st-century skills. The recommendations have been forwarded to the institution’s management for consideration in the centre’s ongoing rehabilitation efforts, aiming to improve professional development and operational effectiveness.